Collectivist information behavior: Mentoring circles as sites for knowledge creation. Issue 1 (27th December 2016) - Given, Lisa M.; Kelly, Wade B.
ABSTRACT: Information behavior research has typically explored individual‐level practices, even within studies of groups and group activities. Although collaborative information seeking has emerged in recent years to explore how people search for and share information, much of this research also focuses on individual‐level experiences. Collectivist approaches to information behavior have been conducted in only a few studies in the discipline; however, collectivism offers a unique, holistic way to study information practices at within‐group levels. Collectivism also accounts for the social, professional, and other contextual elements that shape group members' information practices when pursuing common shared goals. This exploratory qualitative study used focus groups situated in a constructivist grounded theory methodology to investigate wine industry members' experiences while engaging in peer mentoring circles. Designed as a professional development activity, the mentoring circles provided a platform for the development of long‐term relationships among group members to foster information sharing and knowledge creation relevant to their work environments. The emergent results make a significant contribution to the field as they outline key conditions under which collectivist groups support members' information needs. Findings point to the importance of group cohesion developed through shared (industry‐based) language and knowledge and development of kin‐like relationships to generate unique knowledge communities. Interdependency and reciprocity are shown to play key roles in motivating individual group members to share information with their peers.